Cyberfeminism. Old Struggles, New Strategies: The Virtual Escrache as a Tool of Action and Resistance (2020)
In the Information Age there has been a total transformation in each plane of existence in both individual and collective terms. In the midst of these fierce changes, the ways of lin-king in networks and of being-existing in virtual spaces of encounters and disagreements have changed.In this work we set out to inquire about the strategies that women and non-hegemonic sexualities recreate, making use of the possibilities proposed by new technologies, to deal with situations of gender violence. That is how we approached virtual escraches as tools of great potential. We analyze virtual escraches from a case study in Córdoba, Argentina to delve in the senses acquired by escraches and their possible effects.